Coronary Access After Transcatheter Aortic Valve Replacement With Commissural Alignment: The ALIGN-ACCESS Study. (February 2022) - Tarantini, Giuseppe; Nai Fovino, Luca; Scotti, Andrea; Massussi, Mauro; Cardaioli, Francesco; Rodinò, Giulio; Benedetti, Alice; Boiago, Mauro; Matsuda, Yuji; Continisio, Saverio; Montonati, Carolina; Cacciavillani, Luisa; et al.
Abstract : Background: Coronary access (CA) after transcatheter aortic valve replacement (TAVR) with supra-annular transcatheter heart valves (THV) can be challenging. Specific Evolut R/Pro and Acurate Neo THVs orientations are associated with reduced neo-commissure overlap with coronary ostia, while SAPIEN 3 THV cannot be oriented. With the ALIGN-ACCESS study (TAVR With Commissural Alignment Followed by Coronary Access), we investigated the impact of commissural alignment on the feasibility of CA after TAVR. Methods: We performed coronary angiography after TAVR with intra-annular SAPIEN 3, supra-annular Evolut R/Pro, and Acurate Neo THVs in 206 patients. Evolut THVs were implanted aiming for commissure alignment. Alignment of Acurate Neo was retrospectively assessed in 36, intentionally attempted in 26 cases. The primary end point was the rate of unfeasible and nonselective CA after TAVR. Results: Thirty-eight percent of patients received SAPIEN 3, 31.1% Evolut Pro/R, 30.1% Acurate Neo THV. Final valve orientation was favorable to commissural alignment in 85.9% of Evolut and 69.4% of Acurate Neo cases (with intentional alignment successful in 88.5%). Selective CA was higher for SAPIEN 3 than for aligned and misaligned supra-annular THVs (95% versus 71% versus 46%, P <0.001). Cannulation of at least one coronary was unfeasible with 11% misaligned supra-annular, 3% aligned supra-annular, and 0% SAPIEN 3 THVs. Independent predictors of unfeasible/nonselective CA were implantation of a misaligned supra-annular THV (odds ratio, 4.59 [95% CI, 1.81–11.61]; P <0.01), sinus of Valsalva height (odds ratio, 0.83 [95% CI, 0.7–0.98]; P =0.03), and THV–sinus of Valsalva relation (odds ratio, 1.06 [95% CI, 1.02–1.1]; P <0.01). Conclusions: Commissural alignment improves the rate of selective CA after TAVR with supra-annular THVs. Nevertheless, aligned supra-annular THVs carry higher risk of unfeasible/nonselective CA than SAPIEN 3. Patients with a misaligned supra-annular THV, low sinus of Valsalva, and higher THV–sinus of Valsalva relation are at highest risk of impaired CA after TAVR. Abstract : Supplemental Digital Content is available in the text.